Inoculation with Azospirillum brasilense as a strategy to enhance sugarcane biomass production and bioenergy potential - Scudeletti, Daniele [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Momesso, Letusa [UNESP]; Bossolani, João William [UNESP]; Moretti, Luiz Gustavo [UNESP]; De Oliveira, Elisa Fidêncio [UNESP]; Tubaña, Brenda Servaz; Silva, Marcelo de Almeida [UNESP]; de Castro, Sérgio Gustavo Quassi; Hungria, Mariangela (Elsevier, 2023)
Azospirillum inoculation has gained wide prominence as a strategy for fostering both increased sustainability and enhanced agricultural productivity. Plant growth-promoting bacteria such as Azospirillum improve resource use by plants, but proper management of Azospirillum inoculant application in sugarcane (Saccharum spp.) is key to achieving crop yield potential and improving product quality and economic return for farmers. The present study evaluated the application of different doses of A. brasilense inoculant [0, 5, 10, 15 or 20 × 1010 colony forming units (CFU) ha−1] to sugarcane at the setts/sprouting and tillering stages in two crop seasons at two sites under field conditions. The experiment comprised plant cane and first ratoon at Site A and first and second ratoons at Site B. No effects of inoculation on crop nutrition or the technological quality of the raw material were observed. However, the effects of the inoculation on the biometric parameters and yield of sugarcane varied with the dose. The two highest A. brasilense doses (15 and 20 × 1010 CFU ha−1) increased the stalk population and stalk yield of both plant cane and ratoon sugarcane by approximately 2 stalks m−1 and 20 Mg ha−1, respectively. In addition, the two highest inoculation doses promoted increases in sugar and energy production that were consistent with the increase in stalk population and stalk yield. No clear pattern of the effects of inoculant application time on sugarcane was observed. Overall, A. brasilense inoculation promoted sugarcane productivity when applied at high inoculation doses at the sprouting and tillering stages and has the potential to maximize agronomic and economic benefits to the sugarcane sector.
Keywords: Bacterial inoculation; Clean energy; Plant growth-promoting bacteria; Saccharum spp.; Sustainable production